Compensation Charge Control and Modeling for Reproducing Negative Capacitance Effect of Hafnia Ferroelectric Thin Films. Issue 23 (13th October 2020) - Ahn, Dante; Jung, Moonyoung; Lee, Yoseop; Song, Sungmun; Ham, Woori; Suh, Dongseok; Ahn, Seung‐Eon
Abstract: To enable continuing development of the performance of highly integrated semiconductor chips, it is necessary to dramatically lower the power consumption of transistors. The discovery of the negative capacitance (NC) effect and the ferroelectric properties of HfO2 thin films have raised the possibility of surpassing the known physical limitations of the 60 mV subthreshold slope of the current MOSFETs. However, for commercial application, stable reproducibility of the voltage drop effect due to the ferroelectric polarization and a model that can fully interpret this phenomenon must be obtained. Despite intense recent efforts, guidance for the design of devices for mass production based on the NC effect is currently unavailable. This study has directly observed the NC effect and confirmed that the NC effect can be controlled through analysis based on the equivalent circuit theory. It is experimentally verified that the NC effect is caused by an imbalance between the amount of polarization switching and the amount of charge supplied to compensate for such switching in the initial stage of the applied voltage pulse. The results suggest that a gate structure or peripheral circuit that can actively respond to polarization switching is necessary to implement a novel MOSFET with breakthrough power consumption. Abstract : The NC effect can be directly observed by an imbalance between the amount of polarization switching and the amount of compensation charge. The physical phenomena occurring in the ferroelectric thin film are analyzed considering the impedance of each component, and a ferroelectric capacitor equivalent circuit model based on the RC parallel circuit is proposed.